Samuel Johnson and the Impact of Print : (Originally Published As Printing Technology, Letters, and Samuel Johnson). - Kernan, Alvin B (Princeton University Press, 1987)
The description for this book, Samuel Johnson and the Impact of Print: (Originally published as Printing Technology, Letters, and Samuel Johnson), will be forthcoming.